A Preliminary Framework for Preventing Disputes in Different Stages of Building Construction Projects - Nur Nadhirah, Muhammuddin; Mohd Suhaimi, Mohd-Danuri; Mahanim, Hanid; Fadzida, Ismail; Mohd Nasrun, Mohd Nawi (Malaysian Institute Of Planners, 2023)
The upward trend of dispute claims and occurrences throughout different stages has detrimentally affected the outcomes of construction projects. Building upon two major themes from a systematic literature review (SLR) study, Principal Component Analysis (PCA) was performed to further group the extensive causes and strategies into several meaningful groups using the Statistical Social Package Science (SPSS) software. Questionnaires were used and issued to three main stakeholders (clients, consultants, and contractors) in the Klang Valley area. This paper presents the PCA findings, which have led to the development of a framework to prevent disputes in different stages of building construction projects. The PCA findings have narrowed down the major contributors of disputes to “Contract-related causes” and “Time-related causes”. PCA analysis has also shown that the three key themes of “Quality-related strategies,” “Business relationship-related strategies,” and “Productivity-related strategies” were the most effective ways to reduce disagreements. It is important to highlight that the findings related to the causes of disputes during the planning stage consistently align with those of a prior study. This underscores the importance of ethical conduct, particularly during the planning phase and, more specifically, within the tendering process.